Novel Biologically Potent Diorganosilicon(IV) Complexes of Indole-2,3-Dione Derivatives - R. V. Singh; Pooja Nagpal (Bioinorganic Chemistry and Applications)
The aim of the present study is to synthesize some novel ecofriendly fungicides and bactericides of indole-2,3-dione derivatives, having important pharmacodynamic significance. The ligands used in the present account are derived by the condensation of 1,3-dihydro-3-[2-(phenyl)-2-oxoethylidene]-2H-indol-2- one, 1,3-dihydro-3-[2-(4-nitrophenyl)-2-oxoethylidene]-2H-indol-2-one and 1,3-dihydro-3-[2-(4-nitro-3-methylphenyl)- 2-oxoethylidene]-2H-indol-2-one with hydrazinecarboxamide and hydrazinecarbothioamide. These imines, on interaction with diorganosilicon(IV) chlorides, yield complexes having Si–O or Si–S and Si←N bonds. The structure of these compounds have been elucidated by elemental microanalyses and spectral [(UV), (IR), 1H, 13C and 29Si NMR)] studies which unerringly point to a trigonal bipyramidal and octahedral geometries for unimolar and bimolar reactions, respectively. The potency of the synthesized compounds have been assessed by growth inhibiting potential of the complexes against variety of fungal and bacterial strains and male albino rats. The results of these biological studies have been compared with the standard fungicide, Bavistin. The studies demonstrate that, 1,3-dihydro-3-[2-(4-nitrophenyl)-2-oxoethylidene]-2H-indol-2-onehydrazincarbothioamide and its diphenylsilicon(IV) complexes have comparable antimicrobial activity and are less toxic to male albino rats than Bavistin.